Pre-service secondary mathematics teachers' definitions of mathematics terms in their video-lesson presentations: A deductive content analysis - Dejoras, Art Walden A (Archīum Ateneo, 2022)
Taking into account the nature of mathematics as an exact science and the essential role of mathematics teachers’ knowledge of fundamental mathematics definitions; the authors investigated the pre-service secondary mathematics teachers (PSMTs) knowledge of a good mathematics definition in their group video-lesson presentations related to algebra; geometry; descriptive statistics; and number theory. The quality of their definitions can provide a glimpse of their preparedness to teach mathematics at the secondary level. Drawing on Leikin and Zazkis’ (2010) framework to analyze teacher- generated definitions; and Borasi’s (1992) characterizations of a good definition; the authors developed an analytical framework to analyze a total 109 definitions from 90 different mathematical terms. Results reveal that 57 or 52 % of the definitions were weak and suggest PSMTs lack of precision needed in stating definitions of mathematical terms. This could be attributed to PSMTs’ lack of knowledge about the characteristics of a good definition of a mathematical term; and lack of rigor in the use of English language to clearly express the precise meaning of their definitions. The authors recommend PSMTs to be exposed more to activities that would develop their skill in defining. Follow-up studies are also recommended that would further guide mathematics educators in designing intervention programs for the development and improvement of PSMTs’ skills in crafting good mathematical definitions.